BENTHIC HABITAT CLASSIFICATION OF SHALLOW WATER USING WORLDVIEW-2 IMAGERY WITH IN-SITU AND DRONE DATA (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
The Worldview-2 imagery application with groud truth habitat data still has shortcomings that require a long time, limited access, high costs and risk factors. Surveying techniques using drones can reduce these limitations. This study aims to classify and test the accuracy of shallow water habitat classification results in Lancang Island and Sebaru Besar Island from Worldview-2 imagery with ground truth habitat (GTH) and virtual ground truth (VGT) input data and explore the spatial resolution of drone images at altitude different. Overall accuracy results were obtained for 7 habitat classes on Lancang Island with GTH and VGT data of 65.5% and 60.6%, respectively. Whereas in Sebaru Besar Island they were 67.5% and 64.6%, respectively. Comparison of the accuracy of the classification results obtained 4.9% selisi on Lancang Island and 2.9% on Sebaru Besar Island. Significance test results of the GTH and VGT methods on Lancang Island were significantly different with a Z value of 2.0851, while on Sebaru Besar Island it was not significantly different from the Z value of 0.5255, so that benthic habitat mapping with the VGT method could be used as an alternative in-situ field observation, however this still requires further research.